Gaya Bahasa Pada Lirik Lagu Elegi Esuk Pagi Karya Ebiet G. Ade - Nayiroh, Ajmatun; Setiawan, Tovik Agus; Mujahidin, Imam; Khoeriyah, Fitrotul; Azizah, Ririn Nurul; Abror, Muchlas (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The song Elegi Esuk Pagi by Ebiet G. Ade is a form of literary expression in music that has high aesthetic value. The lyrics of this song contain various stylistic elements that contribute to the beauty and deep meaning that the poet wants to convey. This study aims to identify and describe the use of language style in the lyrics of the song Elegi Esuk Pagi with a stylistic approach. The method used in this study is a qualitative descriptive method with reading, listening, and note-taking techniques. The reading technique is used to understand the entire lyrics of the song, the listening technique is carried out by listening to the song repeatedly to identify the emotional nuances and musicality that support the meaning of the lyrics, while the note-taking technique is applied to record and classify the types of language styles found in the lyrics of the song. The results of the study show that Ebiet G. Ade predominantly uses metaphorical language styles, pro toto parts, repetitions, and hyperbole. The use of this language style not only serves to beautify the lyrics, but also to express emotions and reinforce the message that you want to convey to the listener. Thus, this research contributes to understanding the depth of meaning and stylistic aspects in song lyrics as a form of literary work in the world of music